Dark Matter Investigation Using Double Beta Decay Experiments - Francesco Nozzoli; Cinzia Cernetti (Physical Sciences Forum, 2023)
Nuclei that are unstable with respect to double beta decay are potentially interesting for a novel Dark Matter (DM) direct detection approach. In particular, a Majorana DM fermion inelastically scattering on a double beta unstable nucleus could stimulate its decay. Thanks to the exothermic nature of the stimulated double beta decay, this detection approach would allow for also investigating light DM fermions, a class of DM candidates that evade the detection capability of the traditional elastic scattering experiments. The upper limits on the nucleus scattering cross sections and the expected signal distribution for different DM masses are shown and compared with the existing data for the case of the 76Ge nucleus.